The Factors Related with Behaviors and Approaches of Mothers in Avoiding Children from Gastroenteritis - Durduran, Yasemin; Kandemir, Bahar; Pekcan, Sevgi; Evci, Reyhan (Journal of Pediatric Infectious Diseases, 2019)
Gastrointestinal infection is an important public health problem in children and is frequently seen in developing countries due to low socioeconomic status and education levels, not obeying hygiene rules, and lack of environmental sanitation. Prevention of diarrheal diseases and raising the awareness of the mothers about diarrhea/gastroenteritis is a very important subject. The aim of this study was to evaluate the knowledge and attitude of the mothers, who attended a pediatric outpatient clinic for any reason, about the management and prevention of gastroenteritis in children.This cross-sectional study was performed in Konya, Turkey. The study was carried out with mothers who attended the pediatric outpatient clinic of a faculty of medicine and who had a baby between 0 and 2 years of age. Surveys prepared according to the literature, were used for collecting data. Descriptive statistics, chi-square test, and independent t-test were used for data analysis. A p-value of < 0.05 was considered to be significant.The mean age of mothers was 31.7 ± 7.2 years. Of all the mothers, 97.2% had short nails, 76.3% regularly cleaned their nails once a week, and 92.2% used soap for hand washing every time. A mean score of 8.7 ± 2.8 for a question giving 12 situations where hand washing was necessary was obtained. Of the mother's babies, 40.3% had had diarrhea at least once. In terms of giving baby water and changing feeding behavior during diarrhea/gastroenteritis, significant differences were found between mothers whose babies had diarrhea/gastroenteritis previously and those whose babies had not experienced diarrhea/gastroenteritis. 83.6% of mothers had never heard about vaccination against rotavirus.Washing hands correctly and mothers' knowledge about proper water and food hygiene are important points in protecting children against diarrheal and gastroenteritis diseases. However, there is lack of knowledge and good practice, both in protecting children from, and managing children with, diarrhea. Thus, we believe that it would be beneficial to inform and educate mothers with little children, regularly about these issues.
Keywords: gastroenteritis; diarrhea; hygiene; children; prevention